Re-Designing Shariah Monopoly (Monasy) in Islamic Banking Management - Zahro, Nur Fatimatuz; Dahruji, Dahruji; Hakeem, Altan (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to redesign the concept of Sharia contract monopoly as a learning tool within the Islamic banking management course, specifically to enhance students' financial literacy. The development method employed is the 4-D model (Four D Models) according to Thiagarajan, encompassing the stages of define, design, develop, and disseminate, although this research is focused on the development phase. Qualitative methods, including both secondary and primary data collection, are used in this study. The research results indicate that the redesign of the Sharia contract monopoly as an interactive learning tool within the Islamic banking management course deepens students' understanding of Islamic banks, motivating them to master the operational concepts of Islamic banking through property purchase, leasing, and exchange in a simplified economic system. Furthermore, this redesign also plays a role in honing critical thinking, economic calculations, and operational banking analysis.